Testing budget sustainability in Malaysia - Voon, Belinda Mei Yuh (Universiti Malaysia Sarawak (UNIMAS), 2013)
This study examines the sustainability of Malaysian budget deficit for the period of 1970-2011. The study adopts government intertemporal budget constraint as framework and tests the long-run cointegration relationship between government revenue and government expenditure. Johansen cointegration test and Granger causality test have been applied for analysis purpose.